A mixed method study protocol on contributing factors of depression among adults inmates in a local prison Malaysia - Subbarao, Gunenthira Rao; Minhat, Halimatus Sakdiah; Kadir @ Shahar, Hayati; Mukhtar, Firdaus (Human Resource Management Academic Research Society, 2018)
Mental health is a global public health concern. Living in institutions, including imprisonment, make the inmates susceptible to depression. The objective of this research is to determine and explore the contributing factors of depression among adult prison inmates in a Malaysian local prison. The study utilizes the explanatory sequential mixed method approach. In the first phase, the quantitative hypothesis will be used to address the association between depression and biological, psychological, and social factors among the respondents. It will use a validated questionnaire from approximately 456 inmates using random sampling which was constructed based on the Biopsychosocial theory. The level of depression will be measured using the Center for Epidemiology Study Depression Scale (CES-D). In the second phase, in-depth interviews will be steered among depressed inmates recognized through purposive sampling. Univariate, bivariate and multivariate analyses will be used in quantitative statistics, meanwhile, the qualitative phase encompass a series of in-depth interviews where it will be discontinued once the saturation point is attained. The content of the interviews will be recorded and transcribe verbatim using thematic analysis. It is anticipated this study will enlighten the causative factors of depression and will gratify a novel modality to reduce depression.